Revisiting R.S. Belkin’s Criminalistics Course: A Contemporary Take on the Theoretical and Applied Problems of Capturing Information about a Person's Physical Appearance - A. M. Zinin (Теория и практика судебной экспертизы, 2017)
The issues of using forensic methods and tools for capturing information about a person's physical appearance are examined in light of the conceptual provisions regarding the types and forms of capturing such information in the course of procedural actions, as outlined by Professor R.S. Belkin in his Criminalistics Course published in 1997. The paper substantiates their significance to modern investigative efforts towards the identification of wanted criminals.